The application of mechanical diagnosis and therapy in lateral epicondylalgia. (26th May 2016) - Maccio, Joseph R.; Fink, Sarah; Yarznbowicz, Richard; May, Stephen
Abstract : Background : lateral epicondylalgia (LE) is a musculoskeletal diagnosis that causes pain and dysfunction in the lateral aspect of the elbow. Mechanical diagnosis and therapy (MDT) is an orthopaedic classification and treatment system based on mechanical and symptomatic response to repeated and sustained end-range movement. There has been no investigation of the association between MDT and patients diagnosed with LE. Case description : this report presents three patients matching the currently accepted diagnostic criteria for LE, two with a diagnosis of lateral epicondylitis (tennis elbow) from a medical doctor. These patients were classified and treated by a diplomat of MDT and two third-year doctoral students of physical therapy using MDT. Outcomes : short- and long-term (one year) outcomes were excellent, demonstrating rapid abolishment of symptoms and return to prior levels of function in 3–6 visits between 11–59 days. Patients demonstrated the ability to prevent and manage reoccurrence of symptoms independently without seeking further health care. Discussion : this case series raises questions about whether or not the pathologies traditionally associated with the aetiology of LE are actually at fault. Moreover, it raises questions about the utility of special tests typically utilized to identify those structures. The series provides preliminary evidence that MDT may be capable of providing effective short- and long-term outcomes in the management of LE. Level of Evidence: 4